Sophie Pitt-Turnbull discovers America - Sheldon, Dyan. (Cambridge, Mass. : Candlewick Press, 2007)
While spending the summer in Brooklyn with her mother's former schoolmate, Sophie, a sheltered English teenager, makes some unlikely friends and finds a new side to her formerly "dull and passive" personality.
Bulletin (Center for Children's books).
Horn Book.
School Library Journal.
Young Adult
Keywords: Conduct of life -- Juvenile fiction; Interpersonal relations -- Juvenile fiction; Self-confidence -- Juvenile fiction; Vacations -- Juvenile fiction; Conduct of life -- Fiction; Interpersonal relations -- Fiction; Self-confidence -- Fiction; Vacations -- Fiction; Conduct of life -- Fiction; Interpersonal relations -- Fiction; Self-confidence -- Fiction; Vacations -- Fiction; Brooklyn (New York, N.Y.) -- Juvenile fiction; Brooklyn (New York, N.Y.) -- Fiction; Brooklyn (New York, N.Y.) -- Fiction